Analysis of the Teacher's Role in Digital Media-Based Learning Activities Through the Scaffolding Method in Early Childhood Education - Tria Rizky Gantika; Asep Kurnia Jayadinata; Dhea Ardiyanti (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
This study was motivated by the still low levels of literacy and numeracy achievement in Indonesia in the digital era, highlighting the need for teachers to implement innovative learning approaches that are appropriate for the characteristics of early childhood. One approach that can be applied is the digital media-based scaffolding method, which provides gradual assistance to help children learn and complete tasks independently. This study aims to analyze the teacher's role in implementing digital media-based scaffolding for early childhood education in kindergarten. The research employed a descriptive qualitative approach. The participants consisted of one teacher and Group A children aged 4–5 years. Data were gathered through observation, interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data display, and conclusion drawing. The findings show that teachers perform essential roles as educators, facilitators, guides, and motivators in digital media-based learning activities.The most dominant role is that of a guide, as teachers provide gradual assistance through instructions, demonstrations, guiding questions, and direct support until children are able to complete tasks independently. The study concludes that the implementation of digital media-based scaffolding can support early childhood learning when accompanied by optimal teacher involvement. It is expected that the findings of this study will contribute to the development of more effective teaching practices that are aligned with the developmental needs of young children.